STUDI PERBANDINGAN KARAKTER NASIONALISME ANTARA SISWA YANG MENGIKUTI KEGIATAN EKSTRAKURIKULER PASKIBRA DAN PRAMUKA DI SMA NEGERI 4 PEKANBARU - Magdalena Nada Cristine; Hambali Hambali; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Extracurricular activities that have been held by the school is the oneof media that potential for character development and improving the academic qualityof students. Paskibra (flag raisers) and scout are the school’s extracurricular that haveactivity to train student’s characters, for example is line of march and flag raising inthe school that can grow character of nationalism in students. Paskibra and scoutactivities can build character of nationalism, like the leadership attitude of students,bravery, responsibility, and love the country. The aim of this research is to know thedifferences in the character of nationalism between students who join the paskibraextracurricular with scout extracurricular in SMA Negeri 4 Pekanbaru. Subject for thisresearch is members of paskibra and members of scout in SMA Negeri 4 Pekanbaru.Sample taken in this research were 40 people, with 20 members of paskibra and 20members of scout. Method that used for collect the data is methods of observation,interview, and documentation. To analyze the data researcher used quantitativedescriptive techniques with statiscal test. The result of test that receive from percentagecalculation of respondents showed that character of nationalism level of students whojoined paskibra extracurricular in SMA Negeri 4 Pekanbaru is very high, proved byscore results is 81%. While the character of nationalism of student who joined scoutextracurricular in SMA Negeri 4 Pekanbaru is very high too, proved by score results is83,58%. From the result of T-test base on SPSS version 21 that there is no difference incharacter of nationalism between student who joined paskibra extracurricular withscout extracurricular, proved by sig > 5% (0,126 > 0,05) and t arithmetic -0,930smaller than t table 2,0243.Key words: Character of Nationalism, Paskibra Extracurricular, Scout Extracurricular